Relief of post-stroke spasticity with acute vibrotactile stimulation: controlled crossover study of muscle and skin stimulus methods - Seim, Caitlyn; Chen, Bingxian; Han, Chuzhang; Vacek, David; Wu, Laura Song; Lansberg, Maarten; Okamura, Allison (Frontiers in Human Neuroscience, 2023)
Background: Prior work suggests that vibratory stimulation can reduce spasticity and hypertonia.It is unknown which of three predominant approaches (stimulation of the spastic muscle, antagonist muscle, or cutaneous regions) most reduces these symptoms.Objective: Determine which vibrotactile stimulation approach is most effective at reducing spastic hypertonia among post-stroke patients.Methods: Sham-controlled crossover study with random assignment of condition order in fourteen patients with post-stroke hand spasticity. All patients were studied in four conditions over four visits: three stimulation conditions and a sham control. The primary outcome measure was the Modified Ashworth Scale, and the secondary outcome measure was the Modified Tardieu Scale measured manually and using 3D motion capture. For each condition, measures of spastic hypertonia were taken at four time points: baseline, during stimulation, after stimulation was removed, and after a gripping exercise.Results: A clinically meaningful difference in spastic hypertonia was found during and after cutaneous stimulation of the hand. Modified Ashworth and Modified Tardieu scores were reduced by a median of 1.1 (SD = 0.84, p=0.001) and 0.75 (SD = 0.65, p=0.003), respectively, during cutaneous stimulation, and by 1.25 (SD = 0.94, p=0.001) and 0.71 (SD = 0.67, p=0.003), respectively, at 15 minutes after cutaneous stimulation. Symptom reductions with spastic muscle stimulation and antagonist muscle stimulation were non-zero but not significant. There was no change with sham stimulation.Conclusions: Cutaneous vibrotactile stimulation of the hand provides significant reductions in spastic hypertonia, compared to muscle stimulation.1 Seim et al.